Management Audit To Assess The Human Resource Function Of The Finance Department At RSUD Anuntaloko Parigi - Ulla, Safiatul; Ansar, Muhammad (Journal of Applied Accounting, 2025)
This study aims to assess the effectiveness of managing the human resources (HR) function in the finance department of Anuntaloko Parigi Hospital through a management audit approach. Management audit is used as an evaluation tool to measure the extent to which the HR function is carried out effectively in accordance with applicable standards. This research uses descriptive qualitative methods with data collection techniques in the form of interviews and documentation. The audit object includes seven aspects of the HR function, namely planning, recruitment, selection and placement, training and development, performance appraisal, compensation, occupational health and safety, and termination of employment (PHK). The audit results show that most HR functions have run effectively and in accordance with applicable standards. However, weaknesses were found in the aspects of long-term HR planning and recruitment processes that were not fully transparent. This study recommends the need for improvements in job and workload analysis on a regular basis and strengthening the competency-based recruitment system. Management audit is proven to be a strategic tool in identifying weaknesses and encouraging improved HR performance in the hospital environment.